Beyond breathlessness: unveiling chronic cough in interstitial lung diseases. A pilot Portuguese cohort - Flávia Ferreira; Ana Machado; Vânia Fernandes; Tiago Alfaro; Alda Marques; Ana Oliveira (Monaldi Archives for Chest Disease)
Dear Editor, Chronic cough, lasting at least 8 weeks, is a prevalent symptom in individuals with interstitial lung disease, posing significant physical, psychological, and social challenges....